Efficiency of symbiosis between Bradyrhizobium bacteria and soybean plants under various biopreparations - Syromiatnykov Yurii; Yakovlieva Anastasia; Voinash Sergey; Orekhovskaya Alexandra; Vanzha Vladimir; Akhtyamova Leisan; Vashchilin Viktor (BIO Web of Conferences)
The study explores the efficiency of symbiosis between soybean (Glycine max (L.) Merr.) and Bradyrhizobium japonicum under the influence of advanced biopreparations in competitive soil environments. The biopreparations Rizoline-r, Rizotorfin SC, and Bio-gran SC were evaluated for their impact on nodulation, nitrogen fixation activity, biomass production, and yield. Field trials were conducted using a randomized block design, with treatments compared to a non-inoculated control. Rizoline-r demonstrated the highest efficacy, improving nodulation by up to 165%, nitrogenase activity by 238%, and yield by 26.8%. The results underscore the potential of microbial technologies to enhance soybean productivity while reducing reliance on synthetic fertilizers. This research highlights the significance of incorporating biopreparations into sustainable agricultural practices to address global food security challenges.